PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI METODE THE LEARNING CELL SISWA KELAS IV UPT SD NEGERI 150 INPRES TAMALALANG - Nurfadilah; Andi Paida, Amal Akbar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem in this study is How to improve reading comprehension skills through The Learning Cell method in fourth grade students of UPT SD Negeri 150 Inpres Tamalalang. This study aims to determine the improvement of reading comprehension skills through The Learning Cell method in fourth grade students of UPT SD Negeri 150 Inpres Tamalalang. The type of research used in this study is descriptive classroom action research (CAR). Classroom action research is a controlled investigation process to find and solve learning problems in the classroom, the problem-solving process is carried out cyclically, with the aim of improving and increasing the professional services of teachers in handling teaching and learning activities. The subjects in this study were 12 fourth grade students of UPT SD Negeri 150 Inpres Tamalalang. Based on the results of the study, it can be concluded that the use of The Learning Cell method can improve students' reading comprehension skills in the Indonesian language subject in fourth grade UPT SD Negeri 150 Inpres Tamalalang. With student completion in the first cycle test of 33% and in the final test of the second cycle of 83%, it can be said that student learning outcomes have reached the completion criteria. The conclusion of this study is that the use of The Learning Cell method can improve students' reading comprehension skills in Indonesian language subjects.